Squaraine dyes as efficient photoredox catalysts for PET-RAFT polymerization in batch and flow modes accelerated by suppression of dye aggregation - Patil, Anil M.; Nawghare, Indrajeet S.; Nithyanandhan, Jayaraj; Ambade, Ashootosh V. (Macromolecules, 2025)
Organic photoredox catalysts (PCs) based on squaraine dyes are investigated for photoinduced electron transfer-reversible addition-fragmentation chain transfer (PET-RAFT) polymerization under visible-light (lambda max = 485 nm) irradiation in the presence of triethylamine that suppresses self-aggregation of dye and accelerates the polymerization. Several commonly used PCs are also screened, and self-aggregation is found to be reduced with triethylamine, thus providing a simple and effective approach to reduce aggregation of PCs. There is no induction period, and total polymerization time is shorter for squaraine dye PCs than for reported PCs under similar conditions. The photocatalyst system is amenable to polymerization by using different RAFT agents. Methyl methacrylate and a range of functional methacrylates are polymerized with good control over molecular weight and narrow dispersity in a first-order reaction with a random switch ``ON-OFF'' of the light source and even without an inert atmosphere. The mechanism of polymerization without and with requirement of triethylamine is elucidated using control experiments and found to be an oxidative and reductive electron transfer, respectively. A series of diblock and random copolymers of methyl methacrylate with methacrylate monomers are synthesized. Controlled polymerization is also demonstrated using a continuous-flow method and in an aqueous medium.

pH-Responsive and antimicrobial polymer synthesis in continuous flow and effect of pendant alkylamine on the squaraine dye photocatalyst activity - Patil, Anil M.; Nawghare, Indrajeet S.; Siby, Jesna; Bankar, Priyanka M.; Dastager, Syed G.; Rode, Chandrashekhar V.; Nithyanandhan, Jayaraj; Ambade, Ashootosh V. (ACS Applied Polymer Materials, 2026)
pH-responsive and antimicrobial polymers were synthesized by photoinduced electron transfer-reversible addition-fragmentation chain transfer (PET-RAFT) polymerization under blue light (lambda max = 485 nm) using a scalable continuous flow method. The effect of pendant alkylamino groups with different alkyl substituents on methacrylate monomers under blue light is investigated in the absence of a tertiary alkylamine reagent and in the presence of cyanopentanoic acid dithiobenzoate and 4-cyano-4-[(dodecylsulfanylthiocarbonyl) sulfanyl]pentanoic acid as RAFT agents. The rate of polymerization is found to vary with the size of the alkyl chain and with the tertiary, secondary, or quaternary nature of the amino group. The ability of pendant alkylamino groups to transfer electrons to the photocatalyst is shown using cyclic voltammetry and fluorescence quenching experiments; the tendency to suppress dye aggregation is observed using UV-vis spectroscopy; and the rates of polymerization could be correlated with the trend in these results. The mechanism of polymerization is proposed to follow a reductive or oxidative electron transfer pathway depending on the nature of the pendant group. Statistical and diblock copolymers with 2-hydroxyethyl methacrylate are synthesized in batch and continuous flow processes with a comparative study of kinetics in the two methods. The synthesis of high-molecular-weight homopolymer (55,000 g/mol) and statistical copolymer (85,000 g/mol) of N,N-diisopropylaminoethyl methacrylate is shown in continuous flow. The solution self-assembly of diblock copolymers is studied, and the pH-responsive morphology change leading to disassembly is shown. The antimicrobial properties of polymers with a quaternary ammonium pendant group are evaluated. The thermal degradation of statistical copolymers is analyzed.
Keywords: alkylaminoethyl methacrylate; Antimicrobial; continuous flowprocess; PET-RAFT; pH-responsive; self-aggregation